Dalit literature and criticism - Raj Kumar (Literary/cultural theory, 2019)
This book is an attempt to write and develop a critical literary history and theory of Dalit literature. The book grapples with several questions and issues that are key to understanding Dalit voices in literature: Who is a Dalit? What is the history and context of Dalit self-expression? What is the philosophy of Dalit literature? What is Dalit aesthetics? How does one read, interpret and teach Dalit literature? While providing a concise critical survey of the five decades of Dalit literature and criticism, the book deals with Dalit life, culture and history.